-15-3x=0

Simple and best practice solution for -15-3x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15-3x=0 equation:


Simplifying
-15 + -3x = 0

Solving
-15 + -3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + -3x = 0 + 15

Combine like terms: -15 + 15 = 0
0 + -3x = 0 + 15
-3x = 0 + 15

Combine like terms: 0 + 15 = 15
-3x = 15

Divide each side by '-3'.
x = -5

Simplifying
x = -5

See similar equations:

| 12x-y=5 | | 53-3x=15x+15 | | 9-9x=117-37x | | 4A+2A=18 | | 0=-16t^2+167 | | 81-6x=30x+21 | | B+9=14 | | 8-9x=80-23x | | 4x+26=12x-38 | | 1.4-3.2x=3.0 | | 5x-20x^2=0 | | 11x-24=75 | | 0=30+2a^2 | | w^2=21-4w | | h=64t+16t^2 | | h=64t-16t^2 | | -6(x-8)+2x=-(x-9) | | 129-5x=6x+8 | | 73-2x=7x+22 | | 85x-3x=8x+19 | | 22x-55=-22 | | 8n+6=78 | | (1-2x)*(x-3)=2 | | (N-8)*3=30 | | (N+4)*4=36 | | 2x+-8=-12 | | -12n-6(1-9n)=4(10n-5) | | -11(12+p)=-2p+8(p-8) | | 7-7x=155-35x | | 5y-(-2y)= | | 10n-27=63 | | (N-6)*10=20 |

Equations solver categories